PENGARUH POLA KOMUNIKASI INTERPERSONAL TERHADAP PERILAKU AGRESIF SISWA SLA KECAMATAN PANCORAN MAS KOTA DEPOK. - Julynka Widya Putri (2024)
The triggers for aggressive behavior carried out by teenagers are very diverse and aggressive behavior among teenagers can be influenced by several factors, one of which is communication carried out within the family. According to previous research, communication and lack of attention from parents is one of the factors that can cause aggressive behavior in adolescents. Communication in the family context is interaction and collaboration that influences each other between family members. This research aims to test interpersonal communication theory, especially the concept of interpersonal communication patterns which consists of 4 patterns of aggressive behavior and analyze the magnitude of the influence of interpersonal communication patterns on aggressive behavior. Pancoran Mas District, Depok City, was chosen by researchers as the research location because according to data and news from the mass media, there were frequent cases of brawls and bullying in that area. The supporting theory in this research is Interpersonal Communication by Devito who says that there are 5 aspects of effective family communication so that a family can communicate well. The data collection process uses a survey method in the form of a questionnaire with a total of 100 respondents. The results of the Regression Test show that the EqualityPattern has a negative effect on aggressive behavior, which means that the higher the value of the pattern, the lower the aggressive behavior. Meanwhile, the Balanced Split Pattern, Unbalanced Split Pattern and Monopoly Pattern have a positive effect on aggressive behavior, which means that the higher the value of the pattern, the higher the aggressive behavior will be.